FOSTERING SUSTAINABLE PRODUCT DEVELOPMENT: THE INTERPLAY OF GREEN INNOVATION, DYNAMIC CAPABILITIES, AND TECHNOLOGY IN SURABAYA FNB INDUSTRY - Utomo, Septian Sony (Jurnal MBE Manajemen Bisnis, Equilibrium, 2025)
This study investigates the direct effects of Green Product Innovation (GPI) and Green Dynamic Capabilities (GDC) on Green Product Development (GPD), and critically, examines the mediating role of Green Technology (GT) in these relationships within the Food and Beverage (FNB) industry in Surabaya, Indonesia. A quantitative research design was employed, with data collected from 362 FNB owners in Surabaya, Indonesia and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 3.0. The methodology involved rigorous measurement and structural model evaluations, including comprehensive robustness tests, to ensure the stability and generalizability of the findings. The empirical findings consistently supported all seven hypothesized relationships across the original sample and robustness tests, underscoring its pivotal role in fostering sustainable product development. This research addresses a notable gap in the existing literature by empirically elucidating the precise mechanisms through which Green Product Innovation and Green Dynamic Capabilities translate into tangible Green Product Development, particularly by highlighting the crucial mechanistic role of Green Technology in an emerging economy context like Indonesia's FNB industry. This approach moves beyond mere direct correlations to explain the underlying pathways, thereby enriching the theoretical understanding of green innovation, dynamic capabilities, and sustainable product development.